Access to highly functionalized imidazolones bearing α-amino acid esters via KOH-promoted annulation of amidines, nitrosoarenes and malonic esters. Issue 29 (8th July 2021) - Li, Wenhui; Xin, Jie; Zhai, Pingan; Lin, Jianying; Huang, Shuangping; Gao, Wenchao; Li, Xing
Abstract : An efficient approach to obtain highly functionalized imidazolones bearing α-amino acid esters through KOH-mediated one-pot three-component annulation of amidines, nitrosoarenes and malonic esters is reported. Abstract : An efficient approach to obtain highly functionalized imidazolones bearing α-amino acid esters through KOH-mediated one-pot three-component annulation of amidines, nitrosoarenes and malonic esters is reported. This reaction features broad substrate scope, a cheap and readily available promoter, good to high yields for most substrates and mild reaction conditions. The mechanism study shows that the KOH-mediated formation of the imine intermediate via the reaction of nitrosoarenes with malonic esters is a key step.